Soft Power in Central Asia: Actors and Its Activities - M. M. Lebedeva (Vestnik MGIMO-Universiteta)
Article considers theoretical aspects of soft power concept and its use by various actors in Central Asia. It is noted that scholars as well as practitioners are paying insufficient attention to such key concepts position J. Nye, as an attraction. As a result the efficiency of the use of soft power is significantly reduced. It also shows that the attractiveness is not a universal characteristic. For this reason, attractiveness and hence soft power of different actors are different and aimed at different segments of the population. These differences lead to competition of actors, but they do not reduce interaction in the region to zero-sum game. Specific forms and directions of the soft power of Russia, the U.S., the EU and China in Central Asia are discussed. The article emphasizes that the Central Asian states are not just recipients of soft power of external actors, but also themselves form behavioral strategies that are attractive to others.